Government Responsibility for Oil Palm Plantation License That Causes Environmental Damage after the Entrepreneurship of the Copyration Law - Raudiah Raudiah (Budapest International Research and Critics University, 2022)
Oil palm is one of the main commodities in Indonesia based on data from the Central Statistics Agency in 2020 there are 163 oil palm plantation companies. To obtain a plantation business permit, one must meet the requirements set out in Article 45 of the Plantation Law. The enactment of the Job Creation Law Number 11 of 2020, Article 45 is omitted, this has the potential to occur in spatial planning violations, environmental exploitation and has the potential to have an impact on environmental damage. With the enactment of the Job Creation Law which regulates business licenses, in this case, it aims to make it easier for business actors. Based on Government Regulation Number 5 of 2021 concerning Implementation of Risk-Based Business Licensing, the scale of business activities as evidenced by the business registration number (NIB) is divided into four categories, namely low, medium low, medium high and high risk. The granting of oil palm plantation permits is a type of high-risk business because it is related to the environment and the livelihoods of many people. The government can be held accountable by the community for environmental damage that occurs around oil palm plantations. This responsibility is one of the counterbalances in positioning the government's position because it is related to the permits granted. Government responsibility is an obligation for everything or a function to accept the burden as a result of actions taken alone or by other parties. This study uses three research methods, namely statute approach, conceptual approach and historical approach. This research can practically be used as a reference for companies and communities that need legal assistance related to environmental law enforcement, and theoretically can be used as a reference source for research.